DOI: 10.35614/isbn.9789523360952
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian methods applied for ecosystem model calibration and uncertainty source estimation

Abstract: How significant are different uncertainty sources when simulating the future state of the ecosystem in Finland? In this thesis, we examine this question and provide some answers to this broad topic by simulating 21 st century ecosystem conditions with a land-ecosystem model called JSBACH. The results are also compared to similar simulations performed by another model called PREBAS. We consider four different sources of uncertainty that are related to 1) the model that is used to generate the future conditions;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Regardless, the method exhibited equal robustness compared to other state-of-the-art methods for forest inventories. Similarly, Mäkelä (2020) addressed the uncertainty in ecosystem modeling through the Bayesian approach of canonical correlation analysis (CCA; Hotelling, 1937), which is a technique for detecting correlations between two multivariate or random variables and extracting linear components that represent the correlation. The method was equally useful in identifying the uncertainty caused by varied factors on ecosystem modeling.…”
Section: Managing Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless, the method exhibited equal robustness compared to other state-of-the-art methods for forest inventories. Similarly, Mäkelä (2020) addressed the uncertainty in ecosystem modeling through the Bayesian approach of canonical correlation analysis (CCA; Hotelling, 1937), which is a technique for detecting correlations between two multivariate or random variables and extracting linear components that represent the correlation. The method was equally useful in identifying the uncertainty caused by varied factors on ecosystem modeling.…”
Section: Managing Uncertaintymentioning
confidence: 99%
“…For instance, it found that forest management was the dominant factor that contributed to the uncertainty in the study. The idea of identifying uncertainty elements is intriguing, especially with Bayes, as illustrated by Varvia (2018) and Mäkelä (2020).…”
Section: Managing Uncertaintymentioning
confidence: 99%